THE INFLUENCE OF RELIGIOSITY, LITERACY, AND SERVICE QUALITY ON PAYMENT COMPLIANCE VEHICLE TAX IN KUDUS - Wibisono, Merliana; Putu Piastini, Sang Ayu (Jurnal Magister Akuntansi Trisakti, 2024)
This study investigated the influence of religiosity, Knowledge, and quality service of the taxpayer on the vehicle tax payment in Kudus. The data was obtained by spreading the 210 questionnaires in samsat (Sistem Administrasi Manunggal Satu Atap) Kudus. The ten questionnaire data should have been addressed since they were not suitable to be used. Therefore only 200 questionnaires were used. The obtained data was sampled by applying the purposive sampling method. The sample data was then calculated by simple linear regression analysis. The criteria for sampling data were the taxpayer who registered in Samsat Kudus and had tax arrears. The input variables in this study are tax religiosity, taxpayer knowledge, and service quality. Meanwhile, the output variable in this study is motor vehicle tax compliance. Three hypotheses were developed according to the used variables. These developed hypothesis stated that religiosity, Knowledge, and service quality positively affected motor vehicle taxpayer compliance. Following the obtained sampling data, the results showed that three parameters of religiosity, Knowledge, and quality service had a positive effect and were significant to the tax payment of the vehicle. The results were suitable to the developed hypotheses.